2017
DOI: 10.1017/s095457941700147x
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress, FK506 binding protein 5 gene (FKBP5) methylation, and inhibition-related prefrontal function: A prospective longitudinal study

Abstract: Individuals who have experienced high levels of childhood stress are at increased risk for a wide range of behavioral problems that persist into adulthood, yet the neurobiological and molecular mechanisms underlying these associations remain poorly understood. Many of the difficulties observed in stress-exposed children involve problems with learning and inhibitory control. This experiment was designed to test individual’s ability to learn to inhibit responding during a laboratory task. To do so, we measured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 61 publications
(77 reference statements)
4
42
0
1
Order By: Relevance
“…The CpGs found demethylated in prior human studies 26,35,42,7880 and in this report are spatially central to a functional enhancer element that harbors glucocorticoid response elements (GREs) in intron 7 of FKBP5 . These GREs regulate the dynamic transcriptional response of FKBP5 and thus HPA axis activity, the stress response and glucocorticoid negative feedback 26,34,35,42,78,79,81,82 . Our findings in macaques are consistent with that literature, showing that DNA methylation in the central CpG5 position of the FKBP5 intron 7 GRE in the macaque gene influence GR binding in vitro , and are subsequently associated with differential FKBP5 regulation of GR feedback and peripheral cortisol levels.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The CpGs found demethylated in prior human studies 26,35,42,7880 and in this report are spatially central to a functional enhancer element that harbors glucocorticoid response elements (GREs) in intron 7 of FKBP5 . These GREs regulate the dynamic transcriptional response of FKBP5 and thus HPA axis activity, the stress response and glucocorticoid negative feedback 26,34,35,42,78,79,81,82 . Our findings in macaques are consistent with that literature, showing that DNA methylation in the central CpG5 position of the FKBP5 intron 7 GRE in the macaque gene influence GR binding in vitro , and are subsequently associated with differential FKBP5 regulation of GR feedback and peripheral cortisol levels.…”
Section: Discussionsupporting
confidence: 49%
“…Several human studies support a role for FKBP5 DNA demethylation in response to ELS 35,42,7880 . Importantly, a study in survivors of the Holocaust suggested additional intergenerational effects of trauma exposure on FKBP5 DNA methylation in the offspring 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Oshri et al (2017) found that adolescents who reported child abuse and neglect evinced higher levels of impulsive behaviors, and adults who reported child maltreatment evinced compromised DRD. In addition, recent research using fMRI technology demonstrates that early life stress can adversely affect executive control functions that are tied to DRD, such as working memory (Bickel et al, 2011), response inhibition (Harms et al, 2017) and reward salience in both animal (O’Connor, Moloney, Glennon, Vlachou, & Cryan, 2015) and human samples (Birn et al, 2017; Oswald et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…16,17,18,19 Two studies examining response control reported increased responsiveness within the dorsal cingulate cortex and midcingulate cortex and precentral and postcentral gyri during response control in maltreated children and adolescents. 16,17 However, 2 other studies using similar tasks reported that a history of childhood maltreatment in women 18 and a history of exposure to childhood stress in adults 19 were associated with decreased responsiveness in the frontal or frontal-parietal regions of the brain. Moreover, a 2016 study 20 reported a history of childhood maltreatment was associated with significantly reduced activation during sustained attention within regions of the brain in adults, including the left inferior cortex, dorsolateral prefrontal cortex, insula, and temporal cortex, compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%